A new type of amino amide organocatalyzed enantioselective crossed aldol reaction of ketones with aromatic aldehydes. Issue 36 (6th September 2018) - Owolabi, Isiaka A.; Subba Reddy, U.V.; Chennapuram, Madhu; Seki, Chigusa; Okuyama, Yuko; Kwon, Eunsang; Uwai, Koji; Tokiwa, Michio; Takeshita, Mitsuhiro; Nakano, Hiroto
Abstract: A new type of amino amide organocatalysts was designed and synthesized from commercially available amino acids in easy steps. Their catalytic activities were examined in enantioselective crossed aldol reaction of various acyclic and cyclic ketones with aromatic aldehydes to afford the corresponding chiral anti -aldol adducts with good to excellent chemical yields, diastereoselectivities and enantioselectivities (up to 99%, up to syn : anti  = 1:99, up to 97% ee ). Graphical abstract: Image 1